The Impact of Budget Deficit on Economic Growth in an Emerging Market: An Application of the ARDL Technique - Yusuff, Shamsideen Adewale; Abolaji, Abisoye (Asian Development Policy Review, 2020)
The motive of this thesis is to empirically examine the influence of the budget deficit on Nigeria’s growth. This research is based on data from the Central Bank, World Bank and World Development Indicators of Nigeria from 1981 to 2016. To the best of my understanding, there has been no previous study to examine these relationships with all these indicators listed in Nigeria. This study, therefore, proposes to close this literature gap. The main findings are that, in the long term, The ARDL bounds test result reveals that there is a cointegrating relationship between variables. Furthermore, the study revealed that in the long run, gross domestic savings, interest rate, and budget deficit have significant relationship with economic growth while in the short run an only budget deficit and gross domestic savings have a positive influence on economic growth. Various diagnostic tests were carried out to determine whether the model is good. The study concludes that budget deficit has a significant impact on economic growth of Nigeria. Thus, the Keynesian theory is true for Nigeria. Finally, the study recommends that since higher gross domestic savings will lead to an increase in gross domestic investment thereby increasing economic growth. Therefore, there is a need to increase the interest rate to encourage savings in order to accumulate enough resources for investments. Therefore, in the long run, the nation’s productivity level will increase.